1996
DOI: 10.1007/bf01545034
|View full text |Cite
|
Sign up to set email alerts
|

The interactive effect of influence tactic, applicant gender, and type of job on hiring recommendations

Abstract: Abstract:The effects of influence tactic, applicant gender, and job type were examined in the selection context. A male or female applicant used either an assertive, rational, or exchange influence tactic in a simulated job interview script for either a sales representative or cost accounting position. Three hundred four managers, (271 male and 26 female, predominantly white) evaluated the applicant and indicated the likelihood that they would recommend hiring the applicant. Results indicated that tactics were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 20 publications
1
27
0
1
Order By: Relevance
“…However, as mentioned previously, women who display competence during job interviews are less liked and seen as less socially skilled and hirable [21,23]. For instance, competent communication styles used by female job applicants were seen as less persuasive and less hirable to hiring executives than women using less competent communication [10]. This same study found that men who used a competent communication style were seen as the most persuasive and hirable because engaging in behaviors that signal competence (e.g., self-promotion) is normative for men.…”
Section: Self-presentation and Social Normsmentioning
confidence: 83%
“…However, as mentioned previously, women who display competence during job interviews are less liked and seen as less socially skilled and hirable [21,23]. For instance, competent communication styles used by female job applicants were seen as less persuasive and less hirable to hiring executives than women using less competent communication [10]. This same study found that men who used a competent communication style were seen as the most persuasive and hirable because engaging in behaviors that signal competence (e.g., self-promotion) is normative for men.…”
Section: Self-presentation and Social Normsmentioning
confidence: 83%
“…Also, behavior inconsistent with gender stereotypes was related to negative organizational outcomes such as low performance ratings and/or inability to obtain mentoring functions (Tepper et al, 1993). Although a few studies did not reveal a bias against women using (sex-role incongruent) direct influence behavior (Aguinis & Adams, 1998;Izraeli, 1987), some evidence has been obtained showing that male applicants using a direct and assertive strategy when applying for a job are more likely to be recommended for it than females using the same strategy (Buttner & McEnally, 1996).…”
Section: Gender Roles and Socializationmentioning
confidence: 94%
“…The answer appears to be no. Several studies (Buttner & McEnally, ; Carli, ; Reid, Keerie, & Palomares, ), including a meta‐analysis (Eagly et al, ), have shown that women who act like men when in masculine or leadership roles (e.g., assertive language, dominant or directive interpersonal style) are perceived negatively compared with their male counterparts. The devaluation of women in these circumstances is greatest when the evaluators are men (Carli, ; Carli, LaFleur, & Loeber, ; Eagly et al, ; Matschiner & Murnen, ; Reid et al, ).…”
Section: Stereotypes and Gender Rolesmentioning
confidence: 99%
“…Women experts might also be mindful of the social psychological literature showing that women leaders are perceived negatively when they adopt masculine characteristics while serving in “masculine” roles. Given that the expert witness role is traditionally a masculine social role, the literature suggests that women who adopt the role should demonstrate some feminine traits while in the role (e.g., Buttner & McEnally, ; Carli, ; Carli et al, ; Eagly et al, ; Reid et al, ). The particulars of how this might look are not well understood, and thus research is needed to shed light on this question as well.…”
Section: Implications For Men and Women Experts And Attorneys Selectimentioning
confidence: 99%